Journal of Ayurveda and integrative medicine - Indian Institute of Ayurveda & Integrative Medicine (Bangalore, India) (Medknow Publications, 2010)
Explores the relationships between Ayurveda, biomedicine, and other contemporary health sciences.
Keywords: Medicine, Ayurvedic : Periodicals; Medicine, Ayurvedic; Integrative Medicine